Expression and release of platelet protein disulphide isomerase in patients with haemophilia A. (20th October 2016) - Voigtlaender, M.; Holstein, K.; Spath, B.; Bokemeyer, C.; Langer, F.
Abstract : Introduction: Despite similar residual factor VIII activity, patients with haemophilia A (HA) show significant interindividual variability with regard to bleeding frequency and severity, suggesting that additional factors modulate thrombin generation and fibrin deposition. Protein disulphide isomerase (PDI) is an abundant oxidoreductase that exerts pleiotropic effects in primary and secondary haemostasis and contributes to thrombosis and vascular inflammation. Aim: We conducted a pilot study to explore a potential role of platelet PDI in patients with HA. Methods: Expression and release of platelet PDI were studied by flow cytometry and enzyme‐linked immunosorbent assay, respectively. Results: Compared to healthy male controls ( n = 12), patients with HA ( n = 24) showed significantly increased expression of PDI antigen on ADP‐ or TRAP‐6‐, but not on buffer‐treated platelets, a finding that could not be explained by enhanced platelet activation, as indicated by expression of the α‐granule protein, CD62P (P‐selectin). While platelet agonists did not affect PDI secretion in healthy male controls, increased levels of PDI antigen were found in supernatants of TRAP‐6‐treated platelets from patients with HA. Importantly, in two patients with exceedingly high TRAP‐6‐induced PDI release over baseline, findings were consistent when platelets were isolated and stimulated on a separate occasion. No obvious association was found between platelet PDI and bleeding phenotype in this patient cohort. Conclusion: Agonist‐induced expression and release of platelet PDI were increased in patients with HA. Larger studies are needed to clarify if variations in this platelet response contribute to the diversity in bleeding frequency and severity among patients with congenital factor VIII deficiency.